Implementasi Spiritual Accountability Berbasis Nilai-Nilai Islam sebagai Pengendali Internal dalam Mewujudkan Good Governance di Sektor Publik Indonesia - Tadjri Tadjri; Nuril Anwar; Fariz Rahmaditya; Milana Abdillah S. (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Good governance in Indonesia's public sector continues to face serious challenges in the form of corruption, collusion, and nepotism (KKN), despite the existence of comprehensive legal frameworks such as the General Principles of Good Governance (AUPB) and the Government Internal Control System (SPIP). This study aims to analyze the role of Islamic value-based spiritual accountability as an internal control mechanism that can strengthen the realization of good governance. Using a library research method through an integrative content analysis and conceptual synthesis approach, this study examines literature on good governance and AUPB in Indonesian administrative law, public sector accountability and internal control, as well as the concept of spiritual accountability from an Islamic perspective. The synthesis results indicate that spiritual accountability grounded in taqwa, amanah, muhasabah, and ihsan functions as an effective